Improved Salinity Tolerance in Carrizo Citrange Rootstock through Overexpression of Glyoxalase System Genes. (8th July 2015) - Alvarez-Gerding, Ximena; Cortés-Bullemore, Rowena; Medina, Consuelo; Romero-Romero, Jesús L.; Inostroza-Blancheteau, Claudio; Aquea, Felipe; Arce-Johnson, Patricio
Abstract : Citrus plants are widely cultivated around the world and, however, are one of the most salt stress sensitive crops. To improve salinity tolerance, transgenic Carrizo citrange rootstocks that overexpress glyoxalase I and glyoxalase II genes were obtained and their salt stress tolerance was evaluated. Molecular analysis showed high expression for both glyoxalase genes ( BjGlyI and PgGlyII ) in 5H03 and 5H04 lines. Under control conditions, transgenic and wild type plants presented normal morphology. In salinity treatments, the transgenic plants showed less yellowing, marginal burn in lower leaves and showed less than 40% of leaf damage compared with wild type plants. The transgenic plants showed a significant increase in the dry weight of shoot but there are no differences in the root and complete plant dry weight. In addition, a higher accumulation of chlorine is observed in the roots in transgenic line 5H03 but in shoot it was lower. Also, the wild type plant accumulated around 20% more chlorine in the shoot compared to roots. These results suggest that heterologous expression of glyoxalase system genes could enhance salt stress tolerance in Carrizo citrange rootstock and could be a good biotechnological approach to improve the abiotic stress tolerance in woody plant species.